Odpowiedzi

2010-03-23T14:18:42+01:00
2(x+1)-3(x-1)=2x+2-3x+3=-x+5

x(x-1)-3(x²-x)=x²-x-3x²+3=-2x²+2x

5a(a-3)-3a(a-5)=5a do kwadratu-15a-3a do kwadratu +15a=2a do kwadratu
3x(x+1/3 y)-2y(1/2 x-1/2)=3x²+xy-xy+y=3x²+y
1 5 1
Najlepsza Odpowiedź!
2010-03-23T14:19:50+01:00
2(x+1)-3(x-1)= 2x+2-3x+3=-x+5

x(x-1)-3(x²-x)=x²-x-3x²+3x=-2x²+2x

5a(a-3)-3a(a-5)=5a²-15a-3a²+15a=2a²

3x(x+1/3 y)-2y(1/2 x-1/2)=3x²+xy-xy+y=3x²+y

Liczę na najj...
;];]
2010-03-23T14:20:24+01:00
2x+2-3x+3=-1x+5

x<kwadrat>-1x-3x<kwadrat>+3x= -2x<kwadrat>+2x

5a(a-3)-3a(a-5)=5a<kwadrat>-15a-3a<kwadrat>+15a=2a<kwadrat>

3x(x+1/3 y)-2y(1/2 x-1/2)= 3x<kwadrat>+xy-xy+y= 3x<kwadrat>+y
1 5 1